2016
DOI: 10.1093/inthealth/ihw010
|View full text |Cite
|
Sign up to set email alerts
|

Age-targeted HIV treatment and primary prevention as a ‘ring fence’ to efficiently interrupt the age patterns of transmission in generalized epidemic settings in South Africa

Abstract: BackgroundGeneralized HIV epidemics propagate to future generations according to the age patterns of transmission. We hypothesized that future generations could be protected from infection using age-targeted prevention, analogous to the ring-fencing strategies used to control the spread of smallpox.MethodsWe modeled age-targeted or cohort-targeted outreach with HIV treatment and/or prevention using EMOD-HIV v0·8, an individual-based network model of HIV transmission in South Africa.ResultsTargeting ages 20 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…5i and j ). However, because weekly PrEP will likely involve different drugs and may influence efficacy and coverage in unexpected ways, a wider range of efficacy and coverage assumptions were input into the EMOD v2.5 microsimulation model 52 55 , a network transmission model of HIV that includes heterosexual and mother-to-child HIV transmission, calibrated to the HIV epidemic in South Africa 56 – 58 . Assuming that availability of a weekly regimen influences only efficacy and not coverage, the model predicts approximately 200,000 additional infections averted over 20 years—a 3.4% cumulative reduction—by making a weekly PrEP formulation available for high risk populations ages between 15 and 29.…”
Section: Resultsmentioning
confidence: 99%
“…5i and j ). However, because weekly PrEP will likely involve different drugs and may influence efficacy and coverage in unexpected ways, a wider range of efficacy and coverage assumptions were input into the EMOD v2.5 microsimulation model 52 55 , a network transmission model of HIV that includes heterosexual and mother-to-child HIV transmission, calibrated to the HIV epidemic in South Africa 56 – 58 . Assuming that availability of a weekly regimen influences only efficacy and not coverage, the model predicts approximately 200,000 additional infections averted over 20 years—a 3.4% cumulative reduction—by making a weekly PrEP formulation available for high risk populations ages between 15 and 29.…”
Section: Resultsmentioning
confidence: 99%
“…Our results come with the caveat that the failure to achieve 100% suppression is due primarily to steep drop-offs in steps in the treatment cascade that occur subsequent to testing. Under an alternative framework in which testing (rather than linkage to care) is the limiting factor, others have reported that targeting strategies may be optimally directed at slightly older people as prevalence tends to increase with age (Bershteyn et al 2016, Golden et al 2017. Another caveat is that our model ignores the tendency in many societies for younger women to partner with older men (Barbieri andHertrich 2005, Harling et al 2014).…”
Section: Figurementioning
confidence: 95%
“…(5) People are rarely infected by HIV+ partners under the age of 16 (Shisana et al 2014). These last two points suggest that treating people between 16 and 25 can result in "herd immunity" to teenagers entering the sexually active population (Bershteyn et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 shows a typical ‘cascade of care’ used in the EMOD HIV model, and zooms into one component (infant HIV testing) to show how health seeking patterns are user-specified. The baseline model and resulting epidemic and treatment patterns have been systematically compared to country-specific data and other model estimates (Eaton et al 2012 , 2014 , 2015 ), and the ability to flexibly target sub-populations has been used to explore strategies for efficient resource allocation and interrupting onward transmission (Klein, Eckhoff and Bershteyn 2015 ; Bershteyn, Klein and Eckhoff 2016 ). The triggerable campaign framework has also been used to configure reactive case investigation in a spatial malaria model, where treatment of an index case in a household broadcasts the signal for case investigation only to neighboring households (Gerardin et al 2017 ).…”
Section: Supporting Policy and Implementation Planning Through Flexibmentioning
confidence: 99%